Clinical analysis of 48‐h emergency department visit post outpatient extracorporeal shock wave lithotripsy for urolithiasis. Issue 9 (September 2017) - Lu, Chin‐Heng; Kuo, Junne‐Yih; Lin, Tzu‐Ping; Huang, Yi‐Hsiu; Chung, Hsiao‐Jen; Huang, William J.S.; Wu, Howard H.H.; Chang, Yen‐Hwa; Lin, Alex T.L.; Chen, Kuang‐Kuo
Abstract : Background : Patients suffering from renal or ureteral stones can undergo significant discomfort, even when timely diagnosed and treated. The aim of this study was to assess the risk factors and safety of outpatient Extracorporeal Shock Wave Lithotripsy (ESWL) in the management of patients with renal or ureteral stones. Methods : In this study, our cohort consisted of 844 outpatients who underwent outpatient ESWL treated between February 2012 and November 2014 at Taipei Veterans General Hospital. Patients who visited the emergency room (ER) within 48 h after Outpatient ESWL were included in this article. This article analyzes the stone size, stone shape (long to short axis ratio), stone location, previous medical management, urinalysis data, complications and treatment received in the emergency department. Results : Among the 844 initial consecutive patients who underwent outpatient ESWL a total of 1095 times, there were 22 (2%) patients who sought help at our emergency room within 48 h after the outpatient ESWL. Of those 22 patients, the mean age was 54.3 ± 12.6 years, and the BMI was 25.9 ± 3.2. The most common complication complaint was flank pain (55.2%). Other complications included hematuria (13.8%), fever (17.2%), nausea with vomiting (6.9%), acute urinary retention (3.4%) and chest tightness with cold sweating (3.4%). In 22 patients who went back to the ER, 7 patients were admitted to the ward and 1 patient again returned to the ER. All patients received medical treatment without ESWL or surgical management. The meaningful risk factor of ER‐visiting rate following outpatient ESWL within 48 h was stone location, and the renal stones showed statistic significant ( p = 0.047) when compared to ureteral stones. Conclusion : Our study indicated that renal stone contributed to a significantly higher risk of ER‐visiting rate to patients than did ureteral stone, following outpatient ESWL within 48 h. This study confirmed that Outpatient ESWL is a safe treatment for renal or ureteral stones, while inpatient ESWL is not absolutely necessary.